Phosgene Gas Sensing of Ti2CT2 (T = F−, O−, OH−) MXenes. Issue 3 (19th January 2021) - Thomas, Siby; Asle Zaeem, Mohsen
Abstract: The phosgene gas sensing properties of experimentally produced 2D titanium carbide MXenes with surface terminations (Ti2 CT2 : T = F −, O −, OH − ) are studied by first‐principles calculations. The effect of Ti and C vacancy defects, which are frequently created in synthesizing MXenes, on the structural, mechanical, electronic, and gas adsorption properties are studied to analyze the phosgene gas sensing performance of Ti2 CT2 MXenes. Pristine and defective Ti2 C, Ti2 CF2, and Ti2 C(OH)2 show metallicity, making them ideal for gas sensing. Ti (C) vacancy defects in Ti2 CO2, Ti2 CF2, and Ti2 C(OH)2 cause an increase (decrease) in work function, resulting in enhanced interaction between the MXene surface and a gas molecule. When a phosgene gas molecule is exposed on the surface of MXenes, only Ti2 C(OH)2 shows stable adsorption and charge transfer. An ultra‐low recovery time, the time between adsorption and desorption of a phosgene gas molecule, is achieved for both pristine and defective Ti2 C(OH)2 with Ti vacancy. The results elucidate that a Ti2 C(OH)2 based sensor has a high potential for efficient reversible phosgene detection. Abstract : The adsorption properties of phosgene (COCl2 ) gas molecule on pristine and defective Ti2 C and Ti2 CT2 (T= O −, F −, OH − ) MXenes have been studied by employing density functional theory calculations. The results reveal that only Ti2 C(OH)2 shows spontaneous and exothermic adsorption. In the case of Ti2 C, Ti2 CO2, and Ti2 CF2, the computed adsorption energy indicates an endothermic process representing the inert character of COCl2 sensing. Detailed electronic property and charge transfer analyses show efficient and reversible COCl2 gas detection and sensing of the pristine and defective Ti2 C(OH)2 .